Comparative Study of Technologies for Tubule Occlusion and Treatment of Dentin Hypersensitivity - Camilla Berg (Journal of Functional Biomaterials, 2021)
This study aimed to evaluate the occluding/remineralization performance and resistance to acid attacks of the mineralization layer formed by a tooth-desensitizing gel containing amorphous calcium magnesium phosphate (ACMP) particles and compare it to six other desensitizing products available on the market. Similar comprehensive studies are few and there is especially a lack of studies that are up to date. A dentin-disc model was used for in vitro evaluation of the desensitizing toothpastes/gels. Application of the products was performed twice daily for seven days. One set of specimens were evaluated using scanning electron microscopy (SEM) directly after the final treatment and another set was evaluated after an acid challenge, exposing specimens to 2 wt% citric acid. The ACMP desensitizing gel was the only product resulting in complete occlusion by the formation of mineralized material on the dentin surface and inside the tubules. Particle deposition was dominant after treatment with the other desensitizing products, with little or no mineralization, resulting in partial occlusion only. Sensodyne Repair & Protect and Oral-B Pro-Expert showed the highest resistance toward acid attacks. Material inside the tubules remained relatively unaffected by acid attacks in all specimens. The results in this study indicated a great variability among the occluding agents in terms of occlusion and acid resistance of the mineralization layer. The high degree of occlusion and intra-tubular mineralization that could mitigate the effect of acid solubilization indicate that the ACMP desensitizing gel may be a superior option for the treatment of dentin hypersensitivity.